Youth’s underrepresentation in the European Parliament: Insights from interviews with young Members of the European Parliament (MEPs) - Daniel Stockemer; Aksel Sundström (Intergenerational Justice Review)
Why do political parties elect so few young deputies? Given that the quantitative literature has at best only partially answered this question, we decided to conduct a qualitative investigation. Taking the European Parliament as a case for study, we examined this question through interview research with some of the young MEPs who served between 2014 and 2019. Our respondents, who answered various open-ended questions, suggest that the young are so few in number both because they lack contacts within the party and are seen as lacking experience. In addition, it appears that few parties have established pro-active measures to promote young candidates.